Factors that limit educational television in Uganda - Jjuuko, N. Margaret (Kampala : Makerere University, 1998)
Dissertation (Mass Comm.) - Makerere University, 1998
Includes bibliographical references (p. 80-81)
Keywords: Television in education -- Uganda